New approaches to youth in thrill society: sport participation as fuel to boost outlook on future and concepts on self - Perenyi, Szilvia (Applied Studies in Agribusiness and Commerce, 2013)
The theory of “thrill-society” (Schulze 1992) conceptualizes that increased economic status that allows the focus of daily life to switch from providing for physical needs to searching for a meaningful life and self-fulfilment. Combined with the expansion of education, it causes a smooth transition from traditionally inherited social positions and class-based hierarchy in society to a higher degree of social mobility, increased individualisation and diversification of life styles. Noting that, the actualization of this concept in Hungarian society came into effect only along societal discrepancies; still, the uncertainties and insecurities that accompany the process of ‘thrill projects’ collection are substantial. The purpose of this study was to examine the role of sport participation in the lives of young people, how sport may assist young people in coping with the insecurities and uncertainties created in the societal scene that is characterised by the combination of Schulze’s “thrill-society” and the inheritance of political, economic and societal transition of Hungary. Specifically, this study aims to find differences between sport participants and non-participants in their perception of future on micro and macro level, their readiness to take risks and challenges, and their self-concept related to their own health, physical condition, and physical appearance. Stratified random sampling was applied to obtain an accurate representation of Hungarian youth population. Data were analysed by using cross tabulation, non-parametric and multidimensional statistical methods. The results showed that sport participants adopted a more positive image of the future, higher ability to assume risks and a more modern state of mind, as well as a more stable self-concept in comparison to non-participant youth. Also, it seems that the sporting contest may be as strong as sociodemographic positioning in the formulation of these life capabilities. It can be suggested that sport may assist youth with a stable and accountable value environment that reduces the variety of opportunities and provides resources to better deal with societal uncertainties; meanwhile it opens new avenues of personal freedom even in a “thrill society” that filled with deficits in transitioning societies.